A Hysteresis‐free Polymer‐stabilized Blue Phase Liquid Crystal. Issue 1 (June 2014) - Liu, Yifan; Xu, Su; Xu, Daming; Yan, Jing; Wu, Shin‐Tson
Abstract Our experimental results indicate that UV curing conditions dramatically affect the electro‐optic performance of a polymer‐stabilized blue phase liquid crystal (PS‐BPLC). In an IPS cell, the UV light direction, wavelength, and dosage influence the polymer network distribution, operation voltage and hysteresis. By using a longer UV wavelength, we demonstrated a hysteresis‐free PS‐BPLC.